2014
DOI: 10.7307/ptt.v26i4.1256
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Control of High-speed Train Following Operation

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Takagi showed that simple kinematic equation-based control laws are sufficient assuming perfectly synchronous control of multiple trains ( 21 ). Pan and Zheng used an empirical safe-following-distance formula to derive simple control laws sufficient for controlling identical trains that respond instantaneously on a flat track profile ( 22 ). Karredla and Srinivas proposed a quasi-moving-block system with an instantaneous spacing-distance formula and computed the steady-state capacity of the system ( 23 ).…”
Section: Objectives and Previous Researchmentioning
confidence: 99%
“…Takagi showed that simple kinematic equation-based control laws are sufficient assuming perfectly synchronous control of multiple trains ( 21 ). Pan and Zheng used an empirical safe-following-distance formula to derive simple control laws sufficient for controlling identical trains that respond instantaneously on a flat track profile ( 22 ). Karredla and Srinivas proposed a quasi-moving-block system with an instantaneous spacing-distance formula and computed the steady-state capacity of the system ( 23 ).…”
Section: Objectives and Previous Researchmentioning
confidence: 99%
“…Not only the distance difference but also the velocity difference between trains impacts the following train’s movement. 18 Pan and Zheng 19 introduced three control laws based on the velocity and distance difference concept to simulate train’s operation under the MBS. Following their proposed model, the acceleration rate depends on both velocity and distance difference.…”
Section: Train’s Movement Under the Vcsmentioning
confidence: 99%
“…For high‐speed train, the fitting function of safe following distance L s with the velocity V 2 of the following vehicle can be expressed as follows [25] L s = 0.81 V 2 2 + 48.72 V 2 + 281.60 and μ is taken as 0.2, δ is taken as 0.05. The simulation can be seen in Figs.…”
Section: Simulations and Analysismentioning
confidence: 99%